Influence of ligand-water interactions on the aquation of pentacyano (saturated amine) ferrate (ll) ions - Blesa, Miguel A.; Olabe, José A.; Katz, Néstor E.; Aymonino, Pedro J. (1978)
Fil: Blesa, Miguel A. Comisión Nacional de Energía Atómica; Argentina